Structural and vascular assessment of the optic nerve head and macula in chronic Chagas disease - Cristiana L. M. Agra; Camila V. Ventura; Letícia D. da Fonte; Marcela R. V. Oliveira; Marília Leal; Maria Elisa L. S. M. Assunção; Maria da Glória A. M. Cavalcanti; Silvia M. M. Alves; Ana Karine Soares; Liana O. Ventura; Tiago S. Prata (Scientific Reports)
Abstract Chagas disease (CD), a parasitic infection, may have ocular repercussions in its cardiologic form, since a history of heart disease of other etiologies already has been established as a risk factor for neuropathies and maculopathies. The aim of the present study was to investigate preclinical structural and vascular optic nerve head (ONH) and macular parameters in patients with chronic CD. Nineteen patients with CD and 19 healthy subjects were evaluated with optical coherence tomography, optical coherence tomography angiography, and Laguna ONhE® software. The main outcome measures were the glaucoma discriminant factor, average peripapillary retinal nerve fiber layer thickness, macular ganglion cell complex thickness, peripapillary vascular density (VD), foveal and parafoveal thickness, foveal avascular zone area, and total foveal and parafoveal VD from the superficial and deep capillary plexus that were compared between the two groups. No significant differences were observed among the studied variables. Although our findings suggested that the cardiovascular dysfunction resulting from chronic CD does not seem to cause significant structural or vascular preclinical changes to the ONH and the macula, the results herein benefit this patient population and may provide important preliminary information about the ocular impairment caused by the condition and its possible systemic complications.